2017
DOI: 10.1063/1.4979839
|View full text |Cite
|
Sign up to set email alerts
|

Bi2Te3 photoconductive detectors on Si

Abstract: The peculiar properties of the gapless surface states with a Dirac cone shaped energy dispersion in topological insulators (TIs) enable promising applications in photodetection with an ultra-broad band and polarization sensitivity. Since many TIs can be easily grown on silicon (Si) substrates, TIs on Si could make an alternative route for photon detection of Si photonics. We present good device performances of a Si-based single-crystal bismuth telluride (Bi 2 Te 3) photoconductive detector. Room temperature ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The optimum responsivity with the power law dependence can hence be determined. We summarized most of the representative TIs‐based photodetectors in Figure f and Table 1 , where our SnTe photodetector delivers a very large photodetection bandwidth compared to those previously reported TIs‐based photodetectors . The responsivities at four typical working wavelengths of 254, 635, 1550, and 4650 nm, achieve the highest values of 71.11, 49.03, 10.91, and 4.17 A W −1 , respectively.…”
Section: Comparison Of the Photoresponse Performance Of Our Snte Photmentioning
confidence: 78%
“…The optimum responsivity with the power law dependence can hence be determined. We summarized most of the representative TIs‐based photodetectors in Figure f and Table 1 , where our SnTe photodetector delivers a very large photodetection bandwidth compared to those previously reported TIs‐based photodetectors . The responsivities at four typical working wavelengths of 254, 635, 1550, and 4650 nm, achieve the highest values of 71.11, 49.03, 10.91, and 4.17 A W −1 , respectively.…”
Section: Comparison Of the Photoresponse Performance Of Our Snte Photmentioning
confidence: 78%
“…Moreover, TIs have attracted widespread attention and interest in the recent past . The special properties of TIs endow it with great potential in applications such as optoelectronics, spintronics, thermoelectrics, and quantum computations . Most of the reported studies are based on electrical and magnetic transport in TI materials at very low temperatures, where the origin of quantum‐mechanical signatures such as the Aharonov–Bohm oscillation, Shubnikov–de Hass oscillation, linear magnetoresistance (LMR), and weak anti‐localization (WAL) are attributed to the TSS.…”
Section: Comparison Of Parameters Of Different Ti‐based Photodetectorsmentioning
confidence: 99%
“…Thus, the TSS of TI can greatly affect the photocurrent characteristics. Several research groups have demonstrated excellent optical absorption and ultrasensitive broad‐spectrum photodetection in TI materials such as Bi 2 Se 3 films and NWs, polycrystalline Bi 2 Te 3 films, and Sb 2 Te 3 films . Despite numerous studies conducted on TIs, there is little research on the photocurrent generation mechanism caused by TSS.…”
Section: Comparison Of Parameters Of Different Ti‐based Photodetectorsmentioning
confidence: 99%
“…24,25 In addition, topological insulator Bi 2 Te 3 exhibits an excellent surface mobility 26 and good optoelectronic performance. 27 This, combined with the relatively narrow E g of Bi 2 Te 3 and low cost and facile synthesis of Bi 2 Te 3 nanomaterials, has drawn great interest in photodetection, [28][29][30] eld effect transistors, 26,31 spintronics, 32,33 thermoelectrics, 22,34 and lasers. [35][36][37] These advantages of Bi 2 Te 3 merit it to be qualied for the practical application in high-performance optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%